Towards the identification of biomarkers for cystic fibrosis by proteomics - Charro, Nuno Miguel Antunes Garcia, 1983- (2011)
The scope of the work presented in this thesis is to provide identification and characterization of proteins that might contribute to the development and/or progression of the pulmonary disease Cystic Fibrosis (CF), aiming to a better understanding on the proteinaceous environment in several biological samples with influence in the disease. The objectives of this work were in accordance with the actual and to-date Portuguese National Health Plan and were developed in the National Institute of Health Dr. Ricardo Jorge in Lisbon, Portugal, in collaboration with the University of Pittsburgh Medical Centre and the National Cancer Institute at Frederick, both in the United States of America. The involvement of such institutions recalls the importance of this study in trying to unravel mechanisms underlying the development and/or progression of this treatable but incurable disease. This thesis is divided in six chapters which contain results already published or under final preparation for submission to peer reviewed scientific journals of the area, according to point 1 of Artigo 41 from Capítulo V of Regulamento de Estudos Pós- Graduados da Universidade de Lisboa, published in Diário da República, 2ª Série - Nº 209 de 30 de Outubro de 2006. In this context, I hereby state that all the experiments, results and interpretation contained here are original and performed by myself with the collaboration of others where mentioned. The Chapter I corresponds to the General Introduction, where several aspects of the CF’s pathology are approached, since its recognition as an independent disease to the several CF-causing mutations and the phenotype evidenced by the patients. The contribution of several others molecular determinants other than the CFTR alone and the role of Proteomics in these achievements is also described. xxv iii Experimental design, methodologies, results and interpretation are provided in chapters II to V, each one dedicated to a different type of biological sample. Chapter II devotes it to the proteomics characterization of human serum by complementary approaches and integration of the identified species into networks and pathways with biological significance in the context of CF. Chapter III describes the characterization of the CF-associated proteome of mRBC and aims to interpreter previous phenomena reported in these cells of CF patients by the study of altered abundances levels of some relevant proteins. Chapter IV provides a wide molecular portrait of proteins being expressed in the nasal epithelial cells ultimately demonstrating the usefulness of this easily collectable biological sample in mimicking lungs’ microenvironment and its application to the study of respiratory diseases. Chapter V makes use of the deep proteome profiling of nasal epithelial cells and establish correlations and consequences for the impaired respiratory function observed in CF patients. Finally, a General Discussion is presented in Chapter VI were the main conclusions and remarks are pointed hoping to unveil new perspectives on CF while open novel questions to be answered by Proteomics.